Faktor yang Menderteminan Loyalitas Merek Smartphone di Bekasi - Gilang Pratama Hafidz; Dede Herdiansyah (Tamilis Synex: Multidimensional Collaboration, 2024)
Brand loyalty, especially in the smartphone industry is currently one of the most fundamental things to maintain or even to increase the market share. The purpose of this study is to find out what factors meet brand loyalists on smartphones. This type of research is quantitative with purposive sampling techniques which were distributed through questionnaires to 220 respondents of smartphone customers aged 17 – over 55 years who were in the Bekasi area. Primary data analysis was carried out using the Partial Least Square - Structural Equation Modeling (PLS-SEM) method. The results of this study showed only variable of affective commitment that was felt to have no influence on brand loyalty. While the experience of a customer is effective in the audience, the experience of the customer is related to the calculative commitment, the experience of the customer is to the client The calculative of the customer, and the experience of the customer to the ability of the customer has an influence between variables. The results of this study suggest to the next researcher to conduct cluster samples, extend the duration of the study, fill out partial questionnaires and do gender equalization or comparison.